BIOSIMILARS APPROVED FOR PSORIASIS TREATMENT IN EUROPE - Milidrag, Ardea; Lačković, Maja; Dimić, Ivana; Gutić, Medo; Radević, Svetlana; Ravić Nikolić, Ana (PONS - medicinski časopis, 2024)
In recent decades, biologics have emerged as pivotal components in the therapeutic armamentarium, revolutionizing the management of various diseases, including chronic inflammatory skin disorder, the psoriasis. Biosimilars,  biological formulations designed to closely mimic but not replicate existing reference biologic drugs, have heralded a seismic shift in healthcare delivery, promising equitable access to innovative therapies while fostering competition in the pharmaceutical market. The advent of biosimilars has democratized access to effective treatments, alleviating the financial burden on healthcare systems and patients alike, particularly pertinent for conditions like psoriasis, notorious for their exorbitant treatment costs. However, despite their widespread adoption and significant promise, significant challenges remain, requiring ongoing research to comprehensively examine their clinical efficacy, safety profiles, and long-term outcomes.This review aims to present all the biosimilars approved so far in Europe.  Biosimilars represent a transformative force in modern healthcare, but their optimal integration requires careful monitoring, robust pharmacovigilance mechanisms, and ongoing research initiatives to ensure patient safety, build trust among healthcare providers, and maximize treatment efficacy for individuals struggling with psoriasis and other chronic diseases.
Keywords: Keywords: biosimilars; biologic; psoriasis; efficacy; safety; EMA.